Institute of tropical and subtropical cash crops China visits UiTM Perlis - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
UiTM Perlis also received courtesy visit from a delegation of the Institute of Tropical and Subtropical Cash Crops (ITSCC), China on 22 May 2025. The program was part of a working visit and benchmarking initiative focused on tropical crop research, particularly the Harumanis mango plantation. The delegation comprised Assoc. Prof. Zhang Cuixian (Deputy Director of the Institute. Assoc. Prof. Xie Dehong (Senior Researcher), Asst. Prof. Yi Huaifeng (Deputy Director of the Centre). and Asst. Prof. Zhao Aiqiu (Deputy Director of the Center). The delegates were accompanied by Mr. Mohd Saiful Akbar Mohamad Sahal. Head of the Center, Faculty of Plantation and Agrotechnology (FPA). Also present to welcome the delegation were Assoclate Professor Dr. Ahmad Nizan Mat Noor, Rector of UiTM Perlis, along with members of the Senior Executive Management, Head of UITM Perlis' Plantation Unit and FPA lecturers. This visit opens opportunities for strategic collaboration in tropical agriculture research and technology transfer, particularly related to the Harumanis mango which is a proud symbol of Perlis